The Prevalence and Risk Factors for Severe Maternal Morbidities: A Systematic Review and Meta-Analysis - Nik Hazlina, Nik Hussain; Norhayati, Mohd Noor; Shaiful Bahari, Ismail; Mohamed Kamil, Halilul Rahman (Frontiers in Medicine, 2022)
Introduction: Maternal mortality and severe maternal morbidity remain major public health problems globally. Understanding their risk factors may result in better treatment solutions and preventive measures for maternal health. This review aims to identify the prevalence and risk factors of severe maternal morbidity (SMM) and maternal near miss (MNM). Methods: A systematic review and meta-analysis was conducted to assess the prevalence and risk factors of SMM and MNM. The study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. A systematic search was performed in the MEDLINE (PubMed), CINAHL (EBSCOhost), and Science Direct databases for articles published between 2011 and 2020. Results: Twenty-four of the 44 studies included were assessed as being of good quality and having a low risk of bias. The prevalence of SMM and MNM was 2.45% (95% CI: 2.03, 2.88) and 1.68% (95% CI: 1.42, 1.95), respectively. The risk factors for SMM included history of caesarean section (OR [95% CI]: 1.63 [1.43, 1.87]), young maternal age (OR [95% CI]: 0.71 [0.60, 0.83]), singleton pregnancy (OR [95% CI]: 0.42 [0.32, 0.55]), vaginal delivery (OR [95% CI]: 0.11 [0.02, 0.47]), coexisting medical conditions (OR [95% CI]: 1.51 [1.28, 1.78]), and preterm gestation (OR [95% CI]: 0.14 [0.08, 0.23]). The sole risk factor for MNM was a history of caesarean section (OR [95% CI]: 2.68 [1.41, 5.10]). Conclusions: Maternal age, coexisting medical conditions, history of abortion and caesarean delivery, gestational age, parity, and mode of delivery are associated with SMM and MNM. This helps us better understand the risk factors and their strength of association with SMM and MNM. Thus, initiatives such as educational programs, campaigns, and early detection of risk factors are recommended. Proper follow-up is important to monitor the progression of maternal health during the antenatal and postnatal periods.